DNA Binding and Photocleavage Studies of Cobalt(III) Polypyridine Complexes: [Co(en)2PIP]3+, [Co(en)2IP]3+, and [Co(en)2phen-dione]3+ - Penumaka Nagababu; S. Satyanarayana (Bioinorganic Chemistry and Applications)
In this paper, three complexes of type [Co(en)2PIP]3+(PIP=2-phenylimidazo[4,5-f][1,10,] phenanthroline)(1), [Co(en)2IP]3+ (IP=imidazo[4,5-f][1,10,] phenanthroline)(2), and [Co(en)2phen-dione]3+(1,10 phenanthroline 5,6,dione)(3) have been synthesized and characterized by UV/VIS, IR, 1H NMR spectral methods. Absorption spectroscopy, emission spectroscopy, viscosity measurements, and DNA melting techniques have been used for investigating the binding of these two complexes with calf thymus DNA, and photocleavage studies were used for investigating these binding of these complexes with plasmid DNA. The spectroscopic studies together with viscosity measurements and DNA melting studies support that complexes 1 and 2 bind to CT DNA(=calf thymus DNA) by intercalation mode via IP or PIP into the base pairs of DNA, and complex 3 is binding as groove mode. Complex 1 binds more avidly to CT DNA than 2 and 3 which is consistent with the extended planar ring π system of PIP. Noticeably, the two complexes have been found to be efficient photosensitisers for strand scissions in plasmid DNA.